MEMBANGUN JIWA USAHA SANTRI MELALUI PELATIHAN KEWIRAUSAHAAN BERBASIS SYARIAH DI PONDOK PESANTREN NURUS SUNNAH - Eri Prihatmini; Sriwahyuningsih Sulaiman; Dewi Anggraeni; Danu Angga Vebriyanto; Diah Wulansari Hudaya; Filda Hulwani Dewi; Rangga Permana (AMMA : Jurnal Pengabdian Masyarakat, 2026)
Economic independence is an essential competence that must be possessed by the younger generation, including students (santri) in Islamic boarding schools (pesantren), which have traditionally focused on moral and religious education. However, modern economic challenges require santri not only to excel spiritually but also to develop financial literacy and adaptive entrepreneurial insight. This community service program aims to enhance the financial literacy of santri through training in gold investment based on sharia principles, as it is considered a relatively safe, stable, and halal investment instrument. The implementation methods include needs analysis, material development, training sessions, investment simulations, interactive discussions, and evaluation. The results indicate an improvement in santri’s understanding of sharia entrepreneurship concepts, muamalah principles, personal financial management, and their ability to conduct gold investment simulations. Evaluation analysis also shows that participants are able to understand the relationship between entrepreneurship, financial planning, and investment as efforts to achieve economic independence in alignment with Islamic values. This program contributes to strengthening the financial literacy of santri and has the potential to be further developed through continuous mentoring and integration with pesantren-based economic programs.